Perhitungan Harga Pokok Produksi dengan Metode Full Costing dalam Menentukan Harga Jual Produk UMKM - Siti Anisa Afriani; Husni Mubarak (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the calculation of production costs and the determination of selling prices using the full costing method in two micro, small, and medium enterprises (MSMEs), namely SZ.Coconut ART and Parang Syawal Fish Cake. In an increasingly competitive business environment, MSMEs must be able to manage costs efficiently and establish accurate and competitive pricing strategies to maintain their sustainability. The selection of this topic is based on the importance of providing MSMEs with a comprehensive cost analysis tool that incorporates all components of production expenses. This research employs a descriptive quantitative method with a case study approach. Data were collected through in-depth interviews, documentation, and direct observation in both MSMEs located in Bantan District, Bengkalis Regency, Riau. The study reveals that the full costing method provides a completer and more detailed overview of production costs, as it includes raw material costs, direct labor, and factory overhead. The application of this method enables both enterprises to determine more precise and profitable selling prices. The findings highlight that using full costing not only improves pricing accuracy but also enhances decision-making, competitiveness, and financial performance. Overall, the study emphasizes the importance of adopting full costing as a practical cost management tool for MSMEs seeking to strengthen their market position and increase long-term business profitability.